2018
DOI: 10.1016/j.toxrep.2017.12.015
|View full text |Cite|
|
Sign up to set email alerts
|

Mutagenicity and genotoxicity of ClearTaste

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Mutagenic studies on extracts from the plant Euphorbia triaculeata showed that it is not mutagenic and provides protection from the mutagenic effects of cyclophosphamide [31]. A study on a novel taste modulating powder derived from Cordyceps sinensis showed this product was not mutagenic in the Ames test and these results were supported in the micronucleus assay [32]. In a study on the genotoxicity of CBD in Caco-2 cells, 10 μM of CBD did not significantly cause DNA damage after 24 hours of incubation, and CBD was also shown in the comet assay to protect Caco-2 cells from hydrogen peroxide-induced DNA damage [33].…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenic studies on extracts from the plant Euphorbia triaculeata showed that it is not mutagenic and provides protection from the mutagenic effects of cyclophosphamide [31]. A study on a novel taste modulating powder derived from Cordyceps sinensis showed this product was not mutagenic in the Ames test and these results were supported in the micronucleus assay [32]. In a study on the genotoxicity of CBD in Caco-2 cells, 10 μM of CBD did not significantly cause DNA damage after 24 hours of incubation, and CBD was also shown in the comet assay to protect Caco-2 cells from hydrogen peroxide-induced DNA damage [33].…”
Section: Discussionmentioning
confidence: 99%
“…BM-104 mutagenic potential was assessed by detection of mutations in five histidine-dependent Salmonella typhimurium strains [23]. Putative revertant cells (his− to his+) were detected on the basis of their ability to grow in the absence of histidine (required by the parent test strain) after incubation for 48 h with BM-104 (at concentrations from 50 to 5000 μg/plate) or with its potential metabolites that were produced by pre-incubation with a rat liver S9 fraction.…”
Section: Methodsmentioning
confidence: 99%